Adverse in-hospital prognosis in patients with non-ST-segment elevation myocardial infarction with right bundle branch block – red flag ECG and sicker patients. (14th October 2021) - Saraiva, M; Moura, A R; Craveiro, N; Castilho, B; Domingues, K; Pitta, M L; Martins, V; ,
Abstract: Introduction: Recent recommendations regarding myocardial infarction (MI) underline the adverse prognosis associated with right bundle branch block (RBBB), suggesting that, in some cases of non-ST-segment elevation MI (NSTEMI) with RBBB a primary percutaneous coronary intervention (PCI) strategy should be considered. However, it is unclear if this is due to a more difficult and late diagnosis or to the clinical severity inherent to these patients (pts). Purposes: To characterize the NSTEMI with RBBB population and find predictors of worse prognosis. Methods: Retrospective analysis of pts included in the Portuguese Registry of Acute Coronary Syndromes with NSTEMI, comparing pts with RBBB (group A) vs without RBBB (group B), regarding clinical and demographic variables, diagnostic and therapeutic approaches. Primary endpoint was heart failure, electrical and mechanical complications and death in the in-hospital period. Results: We included 9375 pts, 686 in group A and 8689 in group B. Pts in group A were more likely to be male (p<0.001) and over 75 years old (p<0.001). Also, they were more prone to have cardiovascular risk factors (hypertension - p<0.001, diabetes – p<0.001) and history of coronary artery disease (stable angina p=0.007, previous MI p=0.002 and revascularization, either PCI – p=0.016 or surgery – p<0.001), stroke (p<0.001), chronic kidney disease (p<0.001) and cancer (p=0.025), comparing to pts in group B. There were no differences between time from onset of symptoms and first medical contact or hospital admission between groups. Upon admission, these pts presented more frequently with hypotension (p=0.026), Killip class>II (p<0.001) and atrial fibrillation (p<0.001) than pts in group B. There were statiscally significant differences between groups, regarding the use of inotropes (p<0.001), non-invasive (p=0.008) and invasive ventilation (p=0.018) and temporary pacing (p=0.001), all of them higher in group A. Pts with RBBB were less likely to undergo coronary angiography (CA) (p<0.001). However, among those who did, there were no differences in CA timing (p=0.091), but pts from group A had more frequently multivessel disease (p=0.044) and no revascularization was undertaken (p=0.012). About 16.64% of all pts reached the endpoint, but unfavourable in-hospital outcome was significantly more common in group A (p<0.001). RBBB remained an independent predictor of the endpoint (p=0.032) in a multivariate regression analysis, controlled for other variables (namely gender, age, cardiovascular risk factors, previous evidence of cardiovascular disease, and clinical and coronary anatomy data) – AUC of 0.833. Conclusion: Although pts with NSTEMI and RBBB have a poorer in-hospital prognosis, partly due to their bigger clinical complexity (older age, multiple comorbidities and complex coronary anatomy), RBBB itself still remains an independent predictor of worse outcome. FUNDunding Acknowledgement: Type of funding sources: None.